Intrusive busybody or benevolent buddy: phatic communication among Javanese women - Yuli Widiana,; Sumarlam,; Marmanto, Sri; Purnanto, Dwi; Mohamed Zain Sulaiman, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Phatic communication is a discourse mechanism used primarily to establish and maintain social bonds. It operates differently across societies as well as genders within the same society. Thus, failure to understand such differences might result in misunderstanding and communication breakdowns. This paper discusses the phatic communication of the Javanese, the largest ethnic group in Indonesia. We focus primarily on the Javanese women who represent the majority of the Javanese population. Understanding the unique characteristics of their phatic communication would certainly play an important role in the cross-cultural network. The sociopragmatic approach is used for the analytical procedure to scrutinize the characteristics of Javanese women's phatic communication and the data are collected by taking field notes, conducting in-depth interviews, and distributing Discourse Completion Tasks (DCT) questionnaire. The findings show that Javanese women use phatic communication for initiating a conversation, intensifying camaraderie, pleasing others, expressing happiness, and consoling others. The main function is to sustain social rapport. Some phatic talk topics that may be regarded in certain cultures as intrusive and humiliating, such as those which concern one’s private life, are not considered so among Javanese women. To Javanese women, phatic communication is crucial in maintaining and promoting solidarity. Understanding phatic communication among Javanese women would contribute to successful cross-cultural communication in building social networks and business affairs, definitely.